"Programa educativo y nivel de competencias del adulto diabético e hipertenso en un Centro Médico de Huanchaco" - Flores Castañeda, Zaira Clarita (2015)
Quantitative research study, prospective, pre-experimental sort that establish the relationship between the variables (cause and effect), evaluating the effectiveness of an educational program andragogic skill level adult diabetes and hypertension in Huanchaco Medical Center, 2014. Founded on the theoretical basis of knowledge of the continuum of learning in adult Freire (2005) and Pineda (2010); the universe consisted of all adults diagnosed with diabetes and hypertension attending the medical center and the sample was determined in 25 adults who were selected because they met the inclusion criteria; The instrument used was the questionnaire to measure the level of skills of adult diabetes and hypertension, prepared by the author. In processing the data using the SPSS 21 statistical program was created and Marginal homogeneity test Chi square was applied, the test will be significant if the p-value <0.05. The results showed that before applying the educational program, 56 percent of participants had a good level of competence and the remaining 44 percent regular level. After applying the educational program, 92 percent had a good level of competence and the remaining 8 percent obtained a regular level. It is concluded that there is sufficient evidence to state that the educational program at the level of skills of adult diabetes and hypertension was effective (p-value = 0.003).